Depiction of the Balkans on Internet Memes from 9GAG - Veczán, Zoltán (KOME, 2023)
Contrary to all the techno-optimistic expectations regarding the liberating and equalising impacts of online communication – especially of web 2.0 and the emerging social media – stereotypes and oppressive practices are still widespread in discourses on online platforms in many online genres, including Internet memes or meme-aggregating platforms. Researchers have studied many aspects of emergence of stereotypes regarding skin colour, sexual orientation, or gender, but there is a notable research gap in analysing stereotypes towards a special region of Europe: the Balkan Peninsula and its nations. What is more, no research can be found that examines Balkan stereotypes in Internet memes, especially not in a quantitative way on a larger sample. Working with 595 meme specimens from the popular 9GAG portal, this research seeks to learn more about this phenomenon: to find signs of the asymmetric relationship between the Western centrum and the periphery or semi-periphery, as represented by the Balkan states. This study seeks to identify the critical elements of how these stereotypes are displayed, and to compare these elements and their correlations. Another dimension of this research is a review of audience reactions as gauged by “likes”, comments and relative popularity.